FROM “DOVER BEACH” TO “JAKARTA”. A RE-EXAMINATION OF THE ARNOLDIAN CHOICE THROUGH AN INTERTEXTUAL EXERCISE - Octavian MORE (Studia Universitatis Babeș-Bolyai. Philologia, 2017)
From “Dover Beach” to “Jakarta”. A Re-Examination of the Arnoldian Choice through an Intertextual Exercise. By juxtaposing Matthew Arnold’s emblematic poem to texts by Anthony Hecht and Alice Munro, this paper aims at providing a review of some fundamental traits of the Victorian thinker’s “philosophy of pessimism” (“choice”, “renouncement”, “self-effacement”), questioning, at the same time, the social and sexual stereotypes that both unite and differentiate the respective pieces. REZUMAT. De la „Dover Beach” la „Jakarta”. O reexaminare a opțiunii arnoldiene printr-un exercițiu de intertextualitate. Prin alăturarea poemului emblematic al lui Matthew Arnold unor texte de Anthony Hecht și Alice Munro, studiul de față își propune să ofere o reapreciere a câtorva trăsături fundamentale ale „filozofiei pesimismului” ce caracterizează viziunea gânditorului victorian („opțiune”, „renunțare”, „suprimarea eului”), interogând, în același timp, stereotipurile sociale și sexuale care unesc și totodată despart operele în cauză. Cuvinte cheie: Arnold, Hecht, Munro, opțiune, renunțare, pesimism, Plaja de la Dover.